PENGARUH TERAPI TERTAWA TERHADAP PENURUNAN TEKANAN DARAH LANSIA DI UPT PANTI WREDHA BUDHI DHARMA YOGYAKARTA - Niken Setyaningrum; Andri Setyorini; Fachruddin Tri Fitrianta (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
ABSTRACTBackground: Hypertension is one of the most common diseases, because this disease is suffered byboth men and women, as well as adults and young people. Treatment of hypertension does not onlyrely on medications from the doctor or regulate diet alone, but it is also important to make our bodyalways relaxed. Laughter can help to control blood pressure by reducing endocrine stress andcreating a relaxed condition to deal with relaxation.Objective: The general objective of the study was to determine the effect of laughter therapy ondecreasing elderly blood pressure in UPT Panti Wredha Budhi Dharma Yogyakarta.Methods: The design used in this study is a pre-experimental design study with one group pre-posttestresearch design where there is no control group (comparison). The population in this study wereelderly aged over 60 years at 55 UPT Panti Wredha Budhi Dharma Yogyakarta. The method oftaking in this study uses total sampling. The sample in this study were 55 elderly. Data analysis wasused to determine the difference in blood pressure before and after laughing therapy with a ratio datascale that was using Pairs T-TestResult: There is an effect of laughing therapy on blood pressure in the elderly at UPT Panti WredhaBudhi Dharma Yogyakarta marked with a significant value of 0.000 (P 0.05)